Two truths and a lie. It's alive! - Paquette, Ammi-Joan; Thompson, Laurie Ann (Walden Pond Press, 2017)
Features a collection of amazing facts about strange things around us--featuring two strange-but-true stories accompanied by one fictionalized tale. Reveals which are true and how the false stories often have their foundation in reality. Includes maps and color photographs.